2019
DOI: 10.1111/cts.12715
|View full text |Cite
|
Sign up to set email alerts
|

A Double‐Blind, Phase I, Single Ascending Dose Study to Assess the Safety, Pharmacokinetics, and Pharmacodynamics of BOS161721 in Healthy Subjects

Abstract: The purpose of this study was to assess the safety, tolerability, pharmacokinetics, pharmacodynamics, and immunogenicity of BOS161721, a humanized immunoglobulin G1 triple mutation (M252Y/S254T/T256E) monoclonal antibody that inhibits interleukin‐21 (IL‐21) bioactivity. This randomized, single‐center, double‐blind, placebo‐controlled study randomized healthy volunteers 3:1 to single ascending intravenous and subcutaneous doses of BOS161721 (range 1–240 mg) or placebo. BOS161721 and placebo groups had similar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Motavizumab-YTE showed a half-life of around 80 days whereas motavizumab without YTE mutations showed a half-life of only 20–30 days in humans. Based on this impressive report, several engineered mAbs with mutations to increase FcRn binding were evaluated in clinical studies [ 17 – 19 ]. In particular, these mutations have been frequently applied to therapeutic anti-virus antibodies [ 20 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Motavizumab-YTE showed a half-life of around 80 days whereas motavizumab without YTE mutations showed a half-life of only 20–30 days in humans. Based on this impressive report, several engineered mAbs with mutations to increase FcRn binding were evaluated in clinical studies [ 17 – 19 ]. In particular, these mutations have been frequently applied to therapeutic anti-virus antibodies [ 20 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…To determine what types of adverse events could potentially manifest as a result of an anti-IL-21 neutralizing antibody, a comprehensive literature search of compounds blocking IL-21 signaling was carried out. Several anti-IL-21 antibodies (12,13) and an anti-IL-21R antibody (14) were identified and available clinical data were assessed. Overall, a decrease or loss of IL-21 signaling was well-tolerated, but theory and some studies suggested that loss of IL-21 signaling could cause immunosuppression relative to placebo.…”
Section: No Impact Of Immunogenicity On Safety Observedmentioning
confidence: 99%
“…Furthermore, the blockade of IL‐21 function ameliorated CD8 + T cell‐mediated lung fibrosis after bleomycin administration in mice 217 . A human monoclonal antibody, avizakimab, that can inhibit IL‐21 bioactivity, is currently in phase 2 clinical trials for systemic lupus erythematosus (SLE) 218 (NCT03371251). It would be worth exploring the utility of IL‐21 mAb to prevent chronic lung pathology including lung fibrosis following viral infection.…”
Section: Targeting Trm To Resolve or Attenuate Immunopathology In Res...mentioning
confidence: 99%